Polishing composition

By using a polishing agent composed of colloidal silicate, alkali metal salt and water in the CMP process, combined with the effects of oxygen silicate and hydroxide, the problems of over-polishing and recessing of polysilicon films are solved, and the polishing effect with high selectivity and low surface defects is achieved.

JP2025058909AActive Publication Date: 2025-04-09FUJIMI INCORPORATED
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024124258
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-04-09
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

During the CMP process, the polysilicon film buried in the recesses of the silicon oxide film is prone to over-polishing, resulting in depression, and the existing polishing agents have shortcomings in selectivity and surface defects.

Method used

A polishing agent composed of colloidal silicate, alkali metal salt and water is used, with a pH value between 9.0 and 11.5, and an oxygen silica compound is used as the polishing agent of the first layer during the polishing process to change the surface characteristics of the silicate through the action of hydroxide and improve the polishing effect.

Benefits of technology

It effectively reduces the residual polishing of polysilicon and suppresses the recession phenomenon, providing a high selectivity and low surface defect polishing effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058909000002
    Figure 2025058909000002
  • Figure 2025058909000003
    Figure 2025058909000003
  • Figure 2025058909000004
    Figure 2025058909000004
Patent Text Reader

Abstract

To provide a novel polishing composition capable of reducing a residual object to be polished such as polysilicon and suppressing recesses.SOLUTION: A polishing composition comprises colloidal silica, an alkali metal salt, and water, and has a pH of 9.0 to 11.5, wherein: (i) in an object to be polished having a first layer provided with a recess portion and a second layer formed to fill the inside of the recess portion, the polishing composition is used for a step of polishing the second layer to expose the first layer, where the first layer is selected from a layer having an oxygen-silicon bond and a layer having a nitrogen-silicon bond, and the second layer has a silicon-silicon bond; and / or (ii) the number of silanol groups in the colloidal silica is 6 / nm2 or more and 22 / nm2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition. [Background technology]

[0002] In the field of CMP, a silicon dioxide film with a recess and a silicon dioxide film that fills the recess are The polysilicon film is formed, and polishing is performed using the silicon dioxide film as a stopper layer. This can sometimes happen.

[0003] As an index showing how easily a polysilicon film is polished relative to a silicon dioxide film, Selection of the ratio of the rate at which the polysilicon film is polished to the rate at which the silicon dioxide film is polished The ratio is used, which is the rate at which a polysilicon film is polished divided by that of a silicon dioxide film. In order for the silicon dioxide film to function as a stopper layer, a large selectivity is required. It's better to listen.

[0004] Patent Document 1 describes a polishing composition that provides a large selectivity and causes few surface defects. The object of the present invention is to provide a polishing composition comprising an abrasive such as silicon dioxide and water. and may further contain a basic organic compound such as tetramethylammonium hydroxide. A polishing composition is provided. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 10-321569 Summary of the Invention [Problem to be solved by the invention]

[0006] In the process of developing a new polishing composition, the present inventors discovered that the conventional technique does not produce a silicon dioxide film. The polysilicon buried in the recess formed in the step is also over-polished, resulting in the formation of a so-called recess. In the course of further investigation, the present inventors found that the same effect could be observed even if the selectivity was controlled. If the abrasive grains are not suitable or the pH of the polishing composition is not suitable, after polishing, It was found that polysilicon remained or a recess occurred.

[0007] Therefore, the present invention reduces the amount of remaining material to be polished, such as polysilicon, and Furthermore, an object of the present invention is to provide a novel polishing composition which can also suppress recesses. [Means for solving the problem]

[0008] One aspect of the present invention is a composition comprising colloidal silica, an alkali metal salt, and water, the composition having a pH of 9. 0 to 11.5, comprising: (i) a first layer having a recess; and In a polishing object having a second layer formed so as to fill a recess, a step of polishing the layer to expose the first layer, the first layer being an oxygen-silicon bond; or having a nitrogen-silicon bond, and the second layer is selected from those having a nitrogen-silicon bond. and / or (ii) the silanol of said colloidal silica has an isopropyl-silicon bond. Base number is 6 / nm 2 More than 22 pieces / nm 2 The polishing composition is as follows: Effect of the Invention

[0009] According to the present invention, the remaining of the object to be polished, such as polysilicon, is reduced, and In addition, it is possible to provide a novel polishing composition which can also suppress recesses. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of an object to be polished before polishing. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a polished object after ideal polishing. [Diagram 3] FIG. 3 is a schematic cross-sectional view of a polished object that has not been ideally polished and has a recess as a defect. [Figure 4] FIG. 4 is a schematic cross-sectional view of a polished object in which defects that should be polished but are not ideally polished remain. [Diagram 5] FIG. 5 is a schematic cross-sectional view of a ground object showing the defects of FIG. 3 and FIG. 4 occurring simultaneously. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In this specification, "X to Y" are The numerical values ​​(X and Y) are used to mean the lower and upper limits, and "X or more" is used to mean "Y or less." When multiple "X to Y" are listed, for example, "X1 to Y1, Or, if "X2~Y2" is stated, each number is disclosed as the upper limit, and each number is disclosed as the lower limit. All disclosures that include upper and lower limits are disclosed (i.e., supplementary (This is a legitimate basis for the positive result.) Specifically, the correction to X1 or more, the correction to Y2 or less, and the correction to X1 or less Amendments with Y2 or more, amendments with X1 to X2, amendments with X1 to Y2, etc. are all lawful. Also, the features or aspects of the present disclosure should be considered from the perspective of the Markush group. If the above description is provided by a person skilled in the art, the present disclosure will thereby provide a method for the preparation of any individual member of the Markush group. It will be appreciated that the present invention may be described in terms of individual components or subgroups of components. .

[0012] <Polishing composition> One aspect of the present invention is a composition comprising colloidal silica, an alkali metal salt, and water, the composition having a pH of 9. 0 to 11.5, comprising: (i) a first layer having a recess; and In a polishing object having a second layer formed so as to fill a recess, a step of polishing the layer to expose the first layer, the first layer being an oxygen-silicon bond; or having a nitrogen-silicon bond, and the second layer is selected from those having a nitrogen-silicon bond. and / or (ii) the silanol of said colloidal silica has an isopropyl-silicon bond. Base number is 6 / nm 2 More than 22 pieces / nm 2 The polishing composition is as follows. This reduces the amount of remaining material to be polished, such as polysilicon, and also reduces the amount of recesses. It is possible to provide a novel polishing composition that can suppress such a technical effect. The mechanism behind this is thought to be as follows: When the pH of the polishing composition is in the alkaline range, There are hydroxide ions (OH - ) becomes rich, and silicon-ketase such as polysilicon is formed. The surface of the object to be polished that has silanol bonds is converted to silanol groups (SiOH). The polishing target material is converted to silanol groups (SiOH) and the number of silanol groups is within the above range. Hydrogen bonding with rhodium silica promotes the reaction, reducing residues on patterned wafers. In addition, by using an alkali metal salt, it is possible to polish objects having silicon-silicon bonds. It is assumed that the recess is effective in suppressing excessive etching, which causes the However, such a mechanism is merely speculative, and the technical scope of the present invention may be limited by such a mechanism. There are no restrictions.

[0013] In one embodiment of the present invention, the step of polishing the first layer after the first layer is exposed is further included. By further including such a step, the polishing object to be polished, such as polysilicon, This has the technical effect of completely removing any remaining impurities.

[0014] [Abrasive grain] The polishing composition according to one embodiment of the present invention contains colloidal silica as abrasive grains. It has the effect of mechanically polishing the object. Colloidal silica is produced by the sol-gel method. For example, hydrolyzable silicon compounds (e.g., alkoxysilanes, etc.) can be used. It can be obtained by hydrolysis and condensation reactions using benzophenone or its derivatives as raw materials.

[0015] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 6 / nm 2 End 22 pieces / nm 2 The number of silanol groups in colloidal silica is 6 / nm 2 Less than 22 pieces / nm 2 If the thickness is too large, the object to be polished, such as polysilicon, The amount of silanol in colloidal silica may increase or the recess may be accelerated. Base number 6 / nm 2 More than 22 pieces / nm 2 The following methods of control include, for example, colloidal The hydrothermal treatment of a dispersion containing colloidal silica is performed under the conditions of: The dispersion containing the component is heat-treated, for example, at a temperature of 100° C. to 200° C. for 30 to 60 minutes.

[0016] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 6.1 / nm 2 More than 6.2 pieces / nm 2 More than 6.3 pieces / nm 2 More than 6.4 pieces / nm 2 That's it, 6.5 pieces / nm 2 More than 6.6 pieces / nm 2 More than 6.6 pieces / nm 2 Super, 6.7 pieces / nm 2 That's all, 6.8 pieces / nm 2 More than 6.9 pieces / nm 2 More than 7.0 pieces / nm 2 More than 7.1 pieces / nm 2 More than 7.2 pieces / nm 2 More than 7.3 pieces / nm 2 More than 7.4 pieces / nm 2 Above, 7.5 pieces / nm 2 More than 7.6 pieces / nm 2 More than 7.7 pieces / nm 2 More than 7.8 pieces / nm 2 End , 9 pieces / nm 2 More than 10 pieces / nm 2 More than 12 pieces / nm 2 More than 14 pieces / nm 2 That's all, Or 16 / nm 2 That's all.

[0017] According to one embodiment of the present invention, the number of silanol groups in the colloidal silica is 21 / nm 2 Below, 20 pieces / nm 2 Below, 19 pieces / nm 2 Below, 18 pieces / nm 2 Below, 17.5 pieces / n m 2 Less than 17 pieces / nm 2 Below, 16 pieces / nm 2 Below, 15 pieces / nm 2 Below, 14 pieces / n m 2 Below, 13 pieces / nm 2 Below, 12 pieces / nm 2 Below, 11 pieces / nm 2Below, 10 pieces / n m 2 Below, 9 pieces / nm 2 Below, 8 pieces / nm 2 or less than 7 / nm 2 The following is the result. The number of silanol groups is measured by the method described in the Examples.

[0018] According to one embodiment of the present invention, the pulsed NMR specific surface area of ​​the colloidal silica is 40 m 2 / According to one embodiment of the present invention, the pulsed NMR specific surface area of ​​the colloidal silica is But, 39m 2 / g or less, 38m 2 / g or less, 37m 2 / g or less, 36m 2 / g or less, 35 m 2 / g or less, 34m 2 / g or less, 33m 2 / g or less, 32m 2 / g or less, 31m 2 / g Below, 30m 2 / g or less, 29m 2 / g or less, 28m 2 / g or less, 27m 2 / g or less, 2 6m 2 / g or less, 25m 2 / g or less, or 24m 2 / g or less. According to an embodiment, pulsed NMR of colloidal silica is performed at 10 2 / g or more, 15m 2 / g or more, or 20m 2 / g or more. Pulse NM of abrasive grains (especially colloidal silica) The specific surface area was measured by the method described in the Examples. Pulse NMR of colloidal silica The specific surface area changes the relaxation rate of proton resonance depending on the amount of molecules adsorbed on the solid surface. In order to measure the behavior of the colloidal silica, the number of protons in the functional groups on the surface of the colloidal silica can be increased or decreased. This can be done.

[0019] According to one embodiment of the present invention, the average primary particle size of the abrasive grains (particularly colloidal silica) is The limits are 60nm or more, 70nm or more, over 70nm, 71nm or more, 72nm or more, 73nm or more m or more, 74nm or more, 75nm or more, 76nm or more, 77nm or more, 78nm or more, 7 9nm or more, 80nm or more, 81nm or more, 82nm or more, 83nm or more, 84nm or more , 85nm or more, 86nm or more, 87nm or more, 88nm or more, 89nm or more, or , 95 nm or more.

[0020] According to one embodiment of the present invention, the average primary particle size of the abrasive grains (particularly colloidal silica) is The limits are 110nm or less, less than 100nm, 99nm or less, 98nm or less, 97nm or less, 96nm or less, 95nm or less, 94nm or less, 93nm or less, 92nm or less, or According to one embodiment of the present invention, the average primary particle size of the colloidal silica is 91 nm or less. The average primary particle size is more than 70 nm and less than 100 nm. The method for measuring the average primary particle size is described in the Examples. By the method of.

[0021] According to one embodiment of the present invention, the average secondary particle size of the abrasive grains (particularly colloidal silica) is The limits are 110nm or more, 120nm or more, 130nm or more, 140nm or more, and 150nm 160nm or more, 170nm or more, 180nm or more, 190nm or more, 200nm or more, 210 nm or more, or 215 nm or more.

[0022] According to one embodiment of the present invention, the average secondary particle size of the abrasive grains (particularly colloidal silica) is The limits are 350nm or less, 340nm or less, 330nm or less, 320nm or less, and 310nm Below, 300nm or less, 290nm or less, 280nm or less, 270nm or less, 260nm 250nm or less, 240nm or less, 230nm or less, or 225nm or less The average secondary particle size is measured by the method described in the Examples.

[0023] According to one embodiment of the present invention, the average degree of association of the abrasive grains (particularly colloidal silica) (average 2 Secondary particle size / average primary particle size) is 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2 .0 or greater, 2.1 or greater, 2.2 or greater, 2.3 or greater, or 2.4 or greater.

[0024] According to one embodiment of the present invention, the average degree of association of the abrasive grains (particularly colloidal silica) (average 2 Secondary particle size / average primary particle size) is 4.6 or less, 4.4 or less, 4.2 or less, 4.0 or less, 3 .8 or less, 3.6 or less, 3.4 or less, 3.2 or less, 3.0 or less, 2.9 or less, 2.8 or less , 2.7 or less, 2.6 or less, or 2.5 or less.

[0025] According to one embodiment of the present invention, the abrasive grains (particularly colloidal silica) in the polishing composition are The content ratio of F) is 0.01 mass% or more, 0.05 mass% or more, 0.1 mass% or more, 0. 5% by mass or more, 0.6% by mass or more, 0.7% by mass or more, 0.8% by mass or more, 0.9% by mass or more, 1.0% by mass or more, 1.1% by mass or more, 1.2% by mass or more, 1.3% by mass or more, Or, it is 1.4 mass % or more.

[0026] According to one embodiment of the present invention, the abrasive grains (particularly colloidal silica) in the polishing composition are The content ratio of F) is 10% by mass or less, 5% by mass or less, 3% by mass or less, or 2% by mass or less The following is the result.

[0027] According to one embodiment of the present invention, among the abrasive grains contained in the polishing composition, colloidal silica is 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 99.5% by mass or more, or 99.9 mass % or more (upper limit is 100 mass %).

[0028] According to one embodiment of the present invention, the abrasive grains (particularly colloidal silica) contained in the polishing composition are The surface of the (f) is treated to chemically bond a treatment agent such as an organic acid (e.g., sulfonic acid). There is no logic to it.

[0029] [Alkali metal salts] The polishing composition of one embodiment of the present invention contains an alkali metal salt. If the metal salt is not included, the remaining of the polishing object such as polysilicon cannot be reduced. or the formation of a recess may be accelerated.

[0030] According to one embodiment of the present invention, the alkali metal salt is selected from the group consisting of alkali metal hydroxides and According to one embodiment of the present invention, the catalyst comprises at least one of an alkali metal carbonate and an alkali metal hydrate. The alkali metal salt includes a hydroxide of an alkali metal. The hydroxides of alkali metals include potassium hydroxide. Among them, potassium is the most suitable from the viewpoint of reducing the amount of residual metals. is particularly preferred.

[0031] The alkali metal salt also functions as a pH adjuster that adjusts the pH of the polishing composition. According to one embodiment of the present invention, a pH adjuster (particularly an alkali metal The content of the salt is adjusted to a predetermined pH value (particularly, pH value of 9.0 to 11.5) of the polishing composition. It is the appropriate amount to

[0032] According to one embodiment of the present invention, the pH adjuster contained in the polishing composition is an alkali metal Salt (especially potassium hydroxide) is 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more % by mass or more, 99.5% by mass or more, or 99.9% by mass or more (the upper limit is 10 According to one embodiment of the present invention, the pH adjuster contained in the polishing composition is 0.0 mass %. Potassium oxide is 90% by mass or more, 95% by mass or more, 98% by mass or more, 99% by mass or more, 9.5% by mass or more, or 99.9% by mass or more (upper limit is 100% by mass). The abrasive grains (particularly colloidal silica) and the preservatives that may be optionally contained in the polishing composition are Even if it has the function of slightly changing H, its ability to change pH is low, so In this regard, they are not included in the category of pH adjusters.

[0033] [pH] The pH of the polishing composition of one embodiment of the present invention is 9.0 to 11.5. If the value is less than 9.0 or more than 11.5, the polishing object to be polished, such as polysilicon, There is a risk that the amount of remaining material may not be reduced or that recessing may be accelerated.

[0034] According to one embodiment of the present invention, the pH of the polishing composition is 9.1 or more, 9.2 or more, 9. 3 or more, 9.4 or more, 9.5 or more, over 9.5, 9.6 or more, 9.7 or more, 9.8 or more, 9 0.9 or more, or 10.5 or more. According to one embodiment of the present invention, the polishing composition The pH of is 11.5 or less, 11.4 or less, 11.3 or less, 11.2 or less, 11.1 or less, 11 or less, less than 11, 10.9 or less, 10.8 or less, 10.7 or less, 10.6 or less, 10 .5 or less, 10.4 or less, 10.3 or less, 10.2 or less, 10.1 or less, or 9. 8 or less.

[0035] According to one embodiment of the present invention, the pH of the polishing composition is 9.1, 9.2, 9.3, 9. 4, 9.6, 9.7, 9.8, 9.9, 10.1, 10.2, 10.3, 10.4, 10 .5, 10.6, 10.7, 10.8, 10.9, 11.1, 11.2, 11.3, 11 The pH of the polishing composition is not 1.4 or 11.5. The method for measuring the pH of the polishing composition is described in the Examples. By law.

[0036] [Polished object] According to one embodiment of the present invention, the polishing composition comprises a first layer having a recess, and In a polishing object having a second layer formed so as to fill a portion of the polishing surface, FIG. 1 shows a polishing object (before polishing) As shown in the upper diagram of FIG. 1, on an arbitrary film (for example, a Si substrate), The first layer 1 (a film having oxygen-silicon bonds or nitrogen-silicon bonds) is recessed. As shown in the lower diagram of FIG. 1, the inside of the recess is A second layer 2 (a film having silicon-silicon bonds) is formed so as to fill the gap, thereby An object to be polished 10 is formed, which includes a first layer and a second layer.

[0037] When the polishing composition of the present invention is applied to such an object to be polished 10, the polishing composition is polished as shown in FIG. Thus, the polished object 10' is the object to be polished after polishing. The remaining (film having silicon-silicon bonds) is reduced (no remaining) and recesses are also suppressed. In addition, the polishing surface of the present invention has an ideal polished surface in which the surface is controlled (not generated). By applying the composition, the number of metal atoms that may remain after polishing can also be reduced. According to one embodiment, the polished object is polished to a thickness of 1 cm. 2 The number of metal atoms remaining per unit (unit: × 10 10 pieces / cm 2 ) is 40 or less, less than 38, less than 35, 30 or less, 25 or less, 20 or more According to one embodiment of the present invention, the polished object is polished to a size of 1 cm or less. 2 The number of metal atoms remaining per unit (unit: × 10 10 pieces / cm 2 ) is, for example, 0, 0.0 1 or more, 0.5 or more, 1 or more, 5 or more, or 10 or more. First and second layers The object to be polished 10 containing the above was polished with a polishing composition other than the polishing composition of the present invention (i.e., a comparative polishing composition). When polished with the polishing composition, for example, a recess 2a is generated as shown in FIG. Alternatively, the object to be polished (having silicon-silicon bonds) as shown in FIG. The remaining 2b of the film may occur, or, as shown in Figure 5, both may occur simultaneously. Or something like that.

[0038] In one embodiment of the present invention, the object to be polished having an oxygen-silicon bond is ortho TEOS-type silicon oxide (hereafter referred to as TEOS) is produced using tetraethyl silicate as a precursor. (also simply called "TEOS"), HDP (High Density Plasma) , USG (Undoped Silicate Glass), PSG (Phospho rus Silicate Glass), BPSG (Boron-Phospho S ilicate glass), or RTO (Rapid Thermal Ox The TEOS film can be formed by plasma CVD.

[0039] In one embodiment of the present invention, the object to be polished having a nitrogen-silicon bond is silicon nitride. Examples of the first layer include silicon film, silicon carbonitride (SiCN), etc. A silicon oxide film derived from tetraethyl osilicate (TEOS film) is preferable. In one embodiment of the invention, the object to be polished having silicon-silicon bonds is polysilicon. Con, amorphous silicon, single crystal silicon, n-type doped single crystal silicon, p-type doped Examples of the material include single crystal silicon and Si-based alloys such as SiGe. Polycrystalline silicon such as silicon is preferable.

[0040] [Polishing speed] According to one embodiment of the present invention, the polishing composition has a polishing rate of the second layer of 2000 Å / min or more, 2200Å / min or more, 2400Å / min or more, 2600Å / min or more The material has a physical property of 2800 Å / min or more, or 3000 Å / min or more. According to one embodiment of the present invention, the polishing composition has a polishing rate of the second layer of 3500 Å or less. / min or less, or 3200 Å / min.

[0041] According to one embodiment of the present invention, the polishing composition has a polishing rate of the first layer of 60 Å / min. n or more, 70 Å / min or more, 80 Å / min or more, or 90 Å / min or more According to one embodiment of the present invention, the polishing composition has a polishing rate of the first layer. Degree of adhesion is 180Å / min or less, 160Å / min or less, 140Å / min or less, 120Å / min or less, 100Å / min or less, or 95Å / min or less is.

[0042] [Selection ratio] According to one embodiment of the present invention, the polishing composition is The polishing rate (selectivity) of the second layer is 17 to 40, or 20 to 40. If the selectivity is less than 17 or more than 40, the polishing target such as polysilicon is polished. There is a risk that the remaining of the object cannot be reduced or that the recess may be accelerated.

[0043] According to one embodiment of the present invention, the polishing composition has a selectivity of 17 or more, 18 or more, 19 or more, 20 or more, 21 or more, 22 or more, 23 or more, 24 or more, 25 or more, 26 or more, 27 or more, 28 or more, 29 or more, 30 or more, 31 or more, 32 or more, 33 or more, 34 or more, Alternatively, it has a physical property of 35 or more.

[0044] According to one embodiment of the present invention, the polishing composition has a selectivity of 39 or less, 37 or less, It has a physical property of 35 or less, 33 or less, 31 or less, or 29 or less.

[0045] [Transmittance] According to one embodiment of the present invention, the abrasive grains (particularly colloidal silica) contained in the polishing composition When the concentration of ) is 1.5 mass%, the polishing composition is allowed to transmit light with a wavelength of 450 nm. According to this embodiment, the transmittance of the polysilicon By improving the mechanical action on the object to be polished, such as the pattern This is effective in reducing the amount of residue on the wafer. The transmittance can be adjusted to the above range by, for example, The method includes adjusting the particle size of colloidal silica and adjusting the electrical conductivity. can be.

[0046] According to one embodiment of the present invention, the transmittance is 0.13% or more, or 0.5% or more. According to one embodiment of the present invention, the transmittance is 0.9% or less, 0.7% or less, It is less than 0.5%, or less than 0.3%.

[0047] Here, when the abrasive concentration of the polishing composition is not 1.5 mass %, the abrasive concentration is increased to 1.5 mass %. The concentration of abrasive grains in the polishing composition can be adjusted to % by the following method. If the abrasive grain concentration exceeds 1.5 mass%, add an appropriate amount of water so that the abrasive grain concentration is 1.5 mass%. When the abrasive concentration of the polishing composition is less than 1.5 mass %, the abrasive concentration may be increased. The polishing composition may be stored in an environment of 25 to 40° C. until the concentration reaches 1.5% by mass. Alternatively, a process such as ultrafiltration may be carried out.

[0048] [water] The polishing composition of one embodiment of the present invention contains water as an aqueous carrier. According to the paper, the aqueous carrier is an alcohol such as methanol, ethanol, or ethylene glycol. acetone and other ketones; etc., but not limited to, water is included in the aqueous carrier. 0 mass% or more, 95 mass% or more, 98 mass% or more, 99 mass% or more, 99.5 mass% or more , or 99.9% by mass or more (upper limit: 100% by mass).

[0049] [Preservatives] According to one embodiment of the present invention, the polishing composition includes a preservative. For example, 2-methyl-4-isothiazolin-3-one and 5-chloro-2-methyl-4-isothiazolin-3-one Isothiazolinone preservatives such as azolin-3-one, methyl parahydroxybenzoate (parahydrin Methyl paraoxybenzoate), Ethyl parahydroxybenzoate (Ethyl parahydroxybenzoate) and paraoxybenzoic acid ester-based preservatives such as phenoxyethanol. These preservatives may be used alone or in combination of two or more.

[0050] According to one embodiment of the present invention, the polishing composition contains a preservative in an amount of 0.001 to 1 mass %, 0. It may be contained in an amount of 0.005 to 0.5 mass %, or alternatively 0.01 to 0.1 mass %.

[0051] According to one embodiment of the present invention, the number of silanol groups is 6 / nm 2 More than 22 pieces / nm 2 below The composition essentially consists of colloidal silica, an alkali metal salt, a preservative, and water, There is provided a polishing composition having H of 9.0 to 11.5.

[0052] [Other ingredients] The polishing composition of the present invention preferably has a simple structure, that is, silica, an alkali metal salt (especially potassium hydroxide) and water, and optionally It is preferable to contain as few ingredients as possible other than preservatives. Colloidal silica, alkali metals Contains ingredients other than salt (especially potassium hydroxide) and water, and optionally preservatives. In this case, the ratio of the additives (their total) in the polishing composition is 0.1 mass % or less, 0.01 mass % or less. % by mass or less, 0.001% by mass or less, or less than 0.0001% by mass. In the polishing composition, colloidal silica, an alkali metal salt (especially potassium hydroxide) (a) and water and one or more ingredients other than the preservatives that are optionally contained (if there are two or more If the total of the two substances is less than 0.1 mass%, the concentration of the two substances is less than 0.01 mass%, or less than 0.001 mass%. % or less by mass, or less than 0.0001% by mass of the component (or components thereof). is also referred to as being "substantially free."

[0053] According to one embodiment of the present invention, the polishing composition comprises hydroxyethyl cellulose (HEC ), polyacrylic acid (PAA), polyoxyethylene (POE) lauryl ether, dodecyl DBS, hydrogen peroxide (H2O2), ammonia (Ammonium The present invention is substantially free of at least one of amines and amines. According to the present invention, the polishing composition is substantially free of polyoxyalkylene alkyl ether. According to one embodiment of the present invention, the polishing composition contains substantially no alkylarylsulfonic acid. Does not include.

[0054] According to one embodiment of the present invention, a water-soluble polymer, a surfactant, an oxidizing agent, and a nitrogen atom The composition is substantially free of at least one of the compounds having the formula:

[0055] The water-soluble polymer is a polymer that can be dissolved in water at a concentration of 0.5% by mass at the temperature at which the water-soluble polymer is most soluble. When dissolved, it was filtered through a G2 glass filter (maximum pore size 40-50 μm). The mass of the insoluble matter in the water-soluble polymer is 50% or less by mass of the water-soluble polymer added. Examples of the soluble polymer include polyvinyl alcohol (PVA) and polyvinylpyrrolidone. (PVP), pullulan, hydroxyethyl cellulose, and other nonionic water-soluble polymers; Anionic water-soluble polymers such as acrylic acid and carboxymethyl cellulose; and polyacryloyl According to one embodiment of the present invention, The polishing composition is substantially free of at least one of these.

[0056] A surfactant is a substance having a hydrophilic group and a hydrophobic group. Examples of the surfactant include: For example, polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, etc. Alkyl ether type of polyoxyethylene octylphenyl ether; Ether type; Alkyl ester type such as polyoxyethylene laurate; Polyoxyethylene Alkylamine type such as ethylene lauryl amino ether; polyoxyethylene laurate alkylamides such as polyoxyethylene polyoxypropylene ether; Propylene glycol ether type; alkanol amines such as oleic acid diethanolamide allyl phenyl ether type such as polyoxyalkylene allyl phenyl ether Other examples include propylene glycol, diethylene glycol, monoethanolamine, Mine, alcohol ethoxylate, alkylphenol ethoxylate, tertiary acetylene Nonionic surfactants such as glycols and alkanolamides, sodium myristate, Sodium palmitate, sodium stearate, sodium laurate, lauric acid Carboxylic acid type such as potassium sulfate; sulfate ester type such as sodium octyl sulfate; lauryl phosphorus Phosphate esters such as sodium lauryl phosphate, dioctyl sulfosuccinate, sodium Anionic surfactants such as sodium dodecylbenzenesulfonate and other sulfonic acid types cationic surfactants such as amines such as laurylamine hydrochloride, or lecithin, Alkylamine oxide, N-alkyl-N,N-dimethylammonium betaine, etc. Benign surfactants such as alkylbetaines and sulfobetaines are also included. According to the above, the polishing composition is substantially free of at least one of these.

[0057] The oxidizing agent acts to reduce or oxidize the substrate material (especially polysilicon) at the pH at which polishing is performed. The polishing solution may be a material having a redox potential higher than the pH of the polishing solution. The pH of the polishing composition is usually the same as that of the polishing composition. (especially polysilicon) powder is dispersed in water to form a slurry, which is then used for polishing. After adjusting the pH to the same as that of the composition, the redox potential of the slurry was measured using a commercially available redox potentiometer. The value measured by the standard hydrogen electrode at a liquid temperature of 25°C is used. The oxidizing agent may be, for example, hydrogen peroxide, metal oxides, peroxides, nitrates, iodine, etc. Salts, periodates, hypochlorites, chlorites, chlorates, perchlorates, persulfates, heavy salts Chromates, permanganates, organic oxidants, ozonated water, silver(II) salts, iron(III) salts According to one embodiment of the present invention, the polishing composition contains at least one of these salts. Substantially free of one type.

[0058] Examples of compounds having a nitrogen atom include tetramethylammonium and tetraethylammonium. Ammonium, tetrabutylammonium, etc. hydroxides, chlorides, carbonates, sulfates Examples of the salts include tetramethylammonium hydroxide, phosphate salts, etc. tetraethylammonium hydroxide, tetrabutylammonium hydroxide, and other tetrahydroxides Alkyl ammonium, tetramethylammonium carbonate, tetramethylammonium chloride quaternary ammonium compounds such as tetraalkylammonium hydroxide salts, methylamines, etc. , dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine Ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine amine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous Piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine Examples of the amines include perazine, guanidine, and ammonia. According to an embodiment, the polishing composition is substantially free of at least one of these.

[0059] According to one embodiment of the present invention, the polishing composition contains a polymer compound containing a lactam ring. It is not contained, or if it is contained, it is less than 0.0001 mass %.

[0060] According to one embodiment of the present invention, the polishing composition contains substantially no abrasive grains other than colloidal silica. Does not include.

[0061] According to one embodiment of the present invention, the polishing composition has an acid group derived from an organic acid (e.g., It is substantially free of silica having fixed groups (sulfo groups, carboxyl groups, phosphate groups, etc.).

[0062] According to one embodiment of the present invention, the polishing composition is a silica having an amino group fixed to the surface. Qualitatively not included.

[0063] According to one embodiment of the present invention, the polishing composition is substantially free of organic acids.

[0064] In one embodiment of the present invention, the number of silanol groups is 6 / nm2 More than 22 pieces / nm 2 below The colloidal silica is essentially composed of an alkali metal salt and water, and has a pH of 9.0. The polishing composition has a viscosity of 11.5 to 11.5. The above explanations regarding the ingredients (potassium hydroxide for ethanol), water, pH, and preservatives may be applied. The term "essentially composed" means that the polishing composition is composed of colloidal silica, an alkali metal salt (particularly (including potassium hydroxide) and water, and any ingredients other than preservatives that may be included, The ratio of the (total of the) in the polishing composition is 0.1 mass % or less, 0.01 mass % or less This means that the content is below 0.001 mass % or below, or less than 0.0001 mass %.

[0065] In one embodiment of the present invention, the polishing composition may be a one-component type or a two-component type. The polishing composition of one embodiment of the present invention may be, for example, a dilution type. It may be used as a polishing liquid after dilution (typically with water), or it may be used as it is. In other words, the polishing liquid in the technology according to the present invention may be used as a polishing liquid. The concept of a polishing composition includes a polishing agent that is supplied to an object to be polished and used to polish the object to be polished. The composition (working slurry) and the concentrated liquid (working slurry) that is diluted and used for polishing The concentration ratio of the concentrated solution is, for example, 2 to 5 times on a volume basis. It can be about 100 times.

[0066] <Method of manufacturing the polishing composition> In one embodiment of the present invention, a method for producing a polishing composition includes mixing colloidal silica and aluminum. It contains a potassium metal salt (especially potassium hydroxide), water, and optionally a preservative. Therefore, the pH is adjusted to 9.0 to 11.5. Colloidal silica, alkali metal salt (especially potassium hydroxide), water, pH, and preservatives are subject to the above explanations. The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. or higher and 40° C. or lower. Heating may be used to increase the dissolution rate. The mixing time can also be controlled, especially if the mixture is uniformly mixed. Not limited to.

[0067] <Method of polishing the object to be polished> In one embodiment of the present invention, a method for polishing an object to be polished includes the steps of: A first layer 1 (having oxygen-silicon bonds or having nitrogen-silicon bonds) is provided. A second layer 2 (a layer having silicon-silicon bonds) is formed so as to fill the recess. In the polishing object 10 having a polishing layer, the second layer 2 is polished to obtain the first layer 1. In one embodiment of the present invention, the first layer further comprises a step of exposing the first layer to The step of polishing the first layer is included. By further including such a step, the first layer, such as polysilicon, This has the technical effect of completely removing the remaining part of the object to be polished.

[0068] In one embodiment of the present invention, as shown in FIG. A first layer 1 (a layer having an oxygen-silicon bond or a layer having a nitrogen-silicon bond) is formed on the The second layer 2 (silica) is formed so as to fill the recess. A film having silicon-silicon bonds is formed, and the second layer 2 protrudes from the recess of the first layer 1. By laminating such an excessive amount, a polishing object 10 including a first layer 1 and a second layer 2 is formed. Such an object to be polished 10 can be supplied with the polishing composition of the present invention. Polish using a suitable polishing device.

[0069] In one embodiment of the present invention, the polishing apparatus includes a polishing device that holds a substrate having an object to be polished. The polishing pad (polishing cloth) is attached to the holder and the motor with adjustable rotation speed. A typical polishing machine having an attachable polishing platen can be used.

[0070] In one embodiment of the present invention, the polishing pad is made of a general nonwoven fabric, polyurethane, and porous fluororesins, etc. can be used without particular limitation. It is preferable that the grooves are provided so that liquid can be accumulated.

[0071] In one embodiment of the present invention, the polishing conditions include, for example, the rotation of the polishing platen and the carrier. The rotation speed is preferably 10 to 500 rpm or less, independently of each other. The pressure applied to the substrate (polishing pressure) is preferably 0.5 to 10 psi. The method of supplying the composition is not particularly limited, and for example, a method of continuously supplying the composition using a pump or the like can be used. There is no limit to the amount of the polishing composition to be used, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention. It is preferably covered.

[0072] As shown in FIG. 2, by applying the polishing composition of the present invention, the polishing after polishing The polished object 10' is a polished object having a reduced amount of remaining material to be polished ( This results in an ideal polished surface with no residuals and with reduced (no) recesses. EXAMPLES

[0073] The present invention will be described in more detail with reference to the following examples and comparative examples. The technical scope of the present invention is not limited to the following examples. Unless otherwise stated, operations were carried out under the conditions of room temperature (25°C) / relative humidity 40–50% RH.

[0074] <Production of Polishing Composition> The abrasive grains, alkali metal salt, and water were mixed together to obtain the composition shown in Table 1. Thus, a polishing composition was prepared. For example, the polishing composition of Example 1 was prepared by pulse NMR spectroscopy. Surface area is 23.8 m 2 / g, 7.9 silanol groups / nm 2 , and the average primary particle diameter 1.5 mass% of colloidal silica having an average particle size of 90 nm and an average secondary particle size of 220 nm, and The composition contains potassium chloride and water and has a pH of 10.

[0075] <How to calculate particle size> The average primary particle size of the abrasive grains was determined using the “MacsorbHM mod” manufactured by Mountec Co., Ltd. The specific surface area of ​​the abrasive grains measured by the BET method using the EL-1210 and the density of the abrasive grains were The calculations were made based on the above.

[0076] The average secondary particle diameter of the abrasive grains was measured using a dynamic light scattering particle size distribution analyzer U Measured using PA-UT151.

[0077] <How to calculate the number of silanol groups> Number of silanol groups per unit surface area of ​​abrasive grain (unit: silanol groups / nm 2 ) is measured using the following methods After measuring or calculating each parameter by the method described below, .

[0078] More specifically, C in the following formula is the total mass of the abrasive grains, and S in the following formula is the B More specifically, 1.50 g of abrasive grains as solid content is mixed with 200 The mixture was collected in a 100 ml beaker, 100 ml of pure water was added to make a slurry, and then 30 g of sodium chloride was added. Then, add 1N hydrochloric acid to bring the pH of the slurry to 3.0-3. After adjusting the mixture to 5, add pure water until the slurry volume becomes 150 ml.

[0079] An automatic titration device (HIRANUMA SANGYO CO., LTD., COM-1700) was used for this slurry. Then, adjust the pH to 4.0 with 0.1N sodium hydroxide at 25°C. In addition, the amount of 0.1N sodium hydroxide required to raise the pH from 4.0 to 9.0 by pH titration was Measure the volume V [L] of the thorium solution. The average silanol group density (number of silanol groups) is It can be calculated using the following formula.

[0080] ρ = (c × V × N A ) / (C×S) In the above formula, ρ is the average silanol group density (number of silanol groups) (number / nm 2 ) ; c represents the concentration (mol / L) of the sodium hydroxide solution used in the titration; V is the volume (L) of sodium hydroxide solution required to raise the pH from 4.0 to 9.0 Represents; N A represents the Avogadro constant (units / mol); C represents the total mass (solids) of the abrasive grains (g); S is the weighted average value of the BET specific surface area of ​​the abrasive grains (nm 2 / g). The BET specific surface area The stacking was performed using the "MacsorbHM model-1210" manufactured by Mountec Co., Ltd. The specific surface area of ​​the abrasive grains was measured by the BET method.

[0081] <Method for measuring specific surface area using pulsed NMR> Dispersion liquid in which each abrasive grain (raw colloidal silica) is dispersed in water to a concentration of 20% by mass The sample was prepared using a pulsed NMR particle interface characterization system (Xigo). The specific surface area was measured under the following conditions using a 300-millimeter scale (manufactured by Nanotools) and the results are shown in Table 1. As shown in. Measurement conditions Bulk relaxation time: 2409ms Specific surface relaxivity:0.00026 Volume ratio of particle to liquid:0.113 6.

[0082] <Measurement of pH of polishing composition> A glass electrode type hydrogen ion concentration indicator (Horiba Ltd., model number: F-23) was used. The standard buffer solutions (phthalate pH buffer solution, pH: 4.01 (25°C), neutral phosphate pH buffer solution) Buffer pH: 6.86 (25°C), carbonate pH buffer pH: 10.01 (25°C) After three-point calibration, place the glass electrode in the polishing compound and wait for more than two minutes until it stabilizes. The value was measured as the pH of the polishing composition.

[0083] <Measurement of transmittance of polishing composition> The polishing composition was measured using an ultraviolet-visible spectrophotometer (UV-2450, manufactured by Shimadzu Corporation). The transmittance of the polishing composition was measured by irradiating the object with light having a wavelength of 450 nm. The results are shown in Table 1.

[0084] <Measurement of polishing speed> The polishing composition was used to polish the surface of the object to be polished under the following polishing conditions. The target object was a silicon wafer with a 5000 Å thick polysilicon (Poly-Si) film formed on its surface. A silicon wafer (300 mm, blanket wafer) and a 10,000 Å thick wafer on the surface P-TEOS film (TEOS film (silicon dioxide film) formed by plasma CVD) Silicon wafers (300 mm, blanket wafers) prepared by the above-mentioned method were used.

[0085] (polishing conditions) Polishing equipment: Ebara Corporation 300mm CMP single-sided polishing equipment FREX300E Pad: Nitta Haas Co., Ltd. Hard polyurethane pad IC1010 Polishing pressure: 2.2 psi (1 psi = 6894.76 Pa, same below) Polishing platen rotation speed: 70 rpm Carrier rotation speed: 70 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200ml / min Polishing time: 60 seconds.

[0086] The polishing speed was measured using an optical film thickness measuring instrument (ASET-f5x: KLA Tencor (manufactured by the Company) and then divided (thickness before polishing) - (thickness after polishing) by the polishing time. In addition, the polishing rate of the polysilicon film relative to the polishing rate of the P-TEOS film (Å / min) was The ratio of the degree of adhesion (Å / min) was calculated as the selectivity ratio, and the results are shown in Table 1.

[0087] <Polysilicon recess evaluation> Polishing of a patterned wafer with a polysilicon film was performed using a polishing compound under the following [Condition 1]. The patterned wafer was a P-TEOS film (10 After laminating a 1000 Å deep trench, a recess is created, and then polysilicon The recesses were filled with a film (2000 Å).

[0088] The polishing of the above-mentioned polysilicon film-attached patterned wafer was performed without detecting an end point signal. The time from polishing to detection of endpoint signal corresponds to 40% of the polishing time. After a further time, the reaction was terminated. In this way, the first layer (P-TEOS film) was formed. After the exposure, a process of polishing the first layer (P-TEOS film) was further carried out.

[0089] In an isolated wiring area of ​​1 μm width on the surface of a patterned wafer, an atomic force microscope (product name: WA The recess depth was measured using a 300mm diameter mortar (Hitachi Kenki Finetech Co., Ltd.). The resulting recess depth was evaluated according to the following criteria.

[0090] [Condition 1] Polishing equipment: Ebara Corporation 300mm CMP single-sided polishing equipment FREX300E Pad: Nitta Haas Co., Ltd. Hard polyurethane pad IC1010 Polishing pressure: 2.2 psi (1 psi = 6894.76 Pa, same below) Polishing platen rotation speed: 70 rpm Carrier rotation speed: 70 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 200ml / min.

[0091] [Recess amount] The recess was judged according to the following four-level rating criteria. △× is unacceptable for practical use. The results are shown in Table 1.

[0092] ◎: Less than 15 nm ○: 15nm or more and less than 30nm △: 30nm or more and less than 50nm ×: 50 nm or more.

[0093] <Remaining polysilicon (polishing residue)> The thickness of the polysilicon remaining on the P-TEOS film after polishing was measured using an optical thickness measuring instrument ( The thickness was measured using a 1000-millimeter-thick film (ASET-f5x: manufactured by KLA Tencor). The remaining part was evaluated according to the following four-level evaluation criteria. The results are shown in Table 1.

[0094] ◎: Less than 5Å ○: 5 Å or more and less than 10 Å △: 10 Å or more and less than 20 Å ×: 20 Å or more.

[0095] [Metal impurity measurement] After polishing, the silicon wafer with the P-TEOS film was cleaned with a PVA brush. The plate was washed for 60 seconds with deionized water (DIW). Then, the plate was spun for 30 seconds. The concentrations of Na, K, and Li on the wafer surface after cleaning were measured using a TECHNOS The measurements were performed using a total reflection X-ray fluorescence spectrometer (TREX-610T) manufactured by Epson Corporation. The results are shown in Table 1.

[0096] [Table 1]

[0097] <Consideration> The polishing compositions of the examples reduce the amount of polysilicon remaining after polishing and also reduce the amount of re In contrast, the polishing composition of the comparative example was able to suppress the process as shown in Figs. This resulted in some polysilicon that should have been polished remaining and in the promotion of recesses.

[0098] The polishing composition of Example 1 had the best results among all the Examples.

[0099] When polishing was performed using the polishing compositions of Examples 2 and 5, the remaining polysilicon film was slightly thicker. From these results, it was found that the silanolate of the abrasive grain (colloidal silica) The number of holes is 6.6 / nm 2 Super 17.5 pieces / nm 2 It can be seen that less than is preferable. The average primary particle size of the abrasive grains (colloidal silica) is preferably more than 70 nm and less than 100 nm. It becomes clear that...

[0100] When polishing was performed using the polishing composition of Example 3, the amount of sodium remaining as a metal impurity was slightly increased. When polishing was performed using the polishing composition of Example 4, the selectivity was slightly smaller and the reticle was slightly smaller. When polishing was performed with the polishing composition of Example 8, lithium residue was found as a metal impurity. From these results, it was found that potassium hydroxide is the most suitable alkali metal salt. This suggests that there is.

[0101] When polishing was performed using the polishing composition of Example 6, the remaining polysilicon film was slightly thicker and When polishing was performed with the polishing composition of Example 7, some recesses were generated. From these results, it was found that the pH of the polishing composition is preferably more than 9.5 and less than 11. is suggested. [Explanation of symbols]

[0102] 1 first layer, 2 second layer, 2a recess, 2b Remaining second layer to be polished 10 Object to be polished, 10' Polished object.

Claims

1. A solution containing colloidal silica, an alkali metal salt, and water, and having a pH of 9.0 to 11.

5. A polishing composition comprising: (i) a first layer having a recess and a second layer formed to fill the recess; In a polishing object having a layer, a step of polishing the second layer to expose the first layer is performed. The first layer has an oxygen-silicon bond or a nitrogen-silicon bond. wherein the second layer has silicon-silicon bonds. and / or (ii) The number of silanol groups in the colloidal silica is 6 / nm 2 More than 22 pieces / nm 2 Below Below is a polishing composition.

2. A polishing rate of the second layer relative to a polishing rate of the first layer is 20 to 40. Item 2. The polishing composition according to item 1.

3. The colloidal silica has a pulsed NMR specific surface area of ​​40 m 2 / g or less according to claim 1. The polishing composition described above.

4. The average primary particle size of the colloidal silica is more than 70 nm and less than 100 nm.

2. The polishing composition according to claim 1.

5. 2. The polishing composition according to claim 1, wherein the alkali metal salt is a hydroxide of an alkali metal. thing.

6. 6. The polishing composition according to claim 5, wherein the alkali metal hydroxide is potassium hydroxide. thing.

7. HEC, PAA, POE lauryl ether, DBS, H 2 O 2 , ammonia and amine The polishing composition according to claim 1 , which is substantially free of at least one of the following:

8. At least one of a water-soluble polymer, a surfactant, an oxidizing agent, and a compound having a nitrogen atom The polishing composition according to claim 1 , which is substantially free of any of the above.

9. When the concentration of the colloidal silica is 1.5 mass %, the transmittance of light having a wavelength of 450 nm is The polishing composition according to claim 1, wherein the transmittance when the polishing composition is subjected to the polishing is more than 0.1% and less than 1%.

10. Number of silanol groups: 6 / nm 2 More than 22 pieces / nm 2 The following colloidal silica and alkali A polishing composition substantially consisting of a silver metal salt and water, and having a pH of 9.0 to 11.

5. thing.

11. Number of silanol groups: 6 / nm 2 More than 22 pieces / nm 2 The following colloidal silica and alkali The composition essentially consists of a lithium metal salt, a preservative, and water, and has a pH of 9.0 to 11.

5. Polishing composition.

Citation Information

Patent Citations

  • Concentrated composition for fine abrasion of wafer

    JP1992063428A

  • Polishing composition and polishing method

    JP2015196704A

  • Polishing liquid, polishing liquid set and method for polishing substrate

    JP2017149798A

  • Polishing composition, polishing method, and method for manufacturing substrate

    JP2021080441A

  • Polishing composition, polishing method, and semiconductor substrate production method

    JP2022148020A